Relationship Between O Serotype and Virulent Genes in Escherichia Coli Causing Urinary Tract Infections (Iranian Journal of Kidney Diseases, 2011)
Introduction. Escherichia coli are the most frequent pathogens in acute urinary infections. They are classified based on various types of O antigen. Escherichia coli strains that cause urinary tract infections possess several genes encoding urovirulent factors. To assay the relation of virulent factors of E coli in acute urinary infections, the serotypes and virulence factor genotypes were determined.Materials and Methods. We studied 96 E coli isolates from children with acute urinary infections. Four urovirulence determinants were analyzed by DNA colony hybridization, including the genes for type 1 fimbriae (pil), P fimbriae (pap), S fimbriae (sfa), hemolysin (hly), and cytotoxic necrotizing factor 1 (cnf1). O serotypes were also determined.Results. The most frequently found virulence factor-encoding gene in the E coli strains studied was the gene for type 1 fimbriae (27.4%). The prevalence of pap, sfa, hly, and cnf1 were higher in serotypes causing pyelonephritis than cystitis. The most common type of O antigen was O1 (12.2%). There was a significant correlation between serotype and genotype in uropathogenic E coli.Conclusions. The high prevalence of O6 serotypes in children urinary tract infections and the high percentage of virulent genes in serotype O6 suggested a close relation between serotype and genotypes of uropathogen E coli.